THE USE OF SMARTPHONE APPLICATIONS IN ENGLISH LANGUAGE TEACHING AND LEARNING - A. Gumawang Jati (Fakultas Seni Rupa dan Desain ITB, 2018)
In 2002, the number of mobile telephone surpassed the number of ï¬xed lines; and in 2013, the number of smartphones exceeded the number of desktop and laptop computers (Meeker, 2012; The Economist, 2012). This rapid change in technology has changed the process of educating students. Mobile phones, smart phones, tablets have become indispensable to everyone because of their utility and usefulness in language learning if used effectively. Mobile learning has great potential and many researches have been conducted for educational purposes. This paper is aimed for preservice English teachers, teachers and lecturers. The first section of this paper discusses some useful Apps for self-study followed by how to make the most of them. The second section discusses how mobile Apps transform language teaching and learning by elaborating SAMR model in Ruben Puentedura's (R.R. Puentedura, 2011). The use of mobile Apps in supporting the development of core skills which are essential for working in the 21st century will be covered in the last session of this presentation.